1995
DOI: 10.1139/v95-092
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric investigations of aqueous amino acid and dipeptide systems from 288. 15 to 328. 15 K

Abstract: Densities and heat capacities have been measured for aqueous solutions of L-asparagine, L-glutamine, glycylglycine, glycyl-L-valine, glycyl-L-asparagine, and glycyl-DL-leucine at 288. 15,298.15, 313.15, and 328.15 K. These data have been used to calculate apparent molar volumes, V2,0, and apparent molar heat capacities, Cp,2,0, which in turn have been used to obtain standard state volumes, v;, and heat capacities, c;,,.The semi-empirical modelling procedures of Helgeson, Kirkham, and Flowers have been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Heat-of-mixing flow calorimetry has been used to determine ionization constants and enthalpies of reaction for the protonation of the amino and carboxylate groups of several amino acids at temperatures of up to 125°C (Izatt et al, 1992;Gillespie et al, 1995;Wang et al, 1996). Vibrating-tube densimeters and a Picker-type flow microcalorimeter have recently been used to determine experimental values for the standard partial molar volumes and heat capacities of glycine, ␣-alanine, ␤-alanine, proline, and the dipeptide glycyl-gylcine, at temperatures as high as 275°C (Hakin et al, 1995(Hakin et al, , 1998Clarke and Tremaine, 1999;. We are aware of no other experimental studies on the thermodynamic properties of aqueous amino acids or peptides above 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-of-mixing flow calorimetry has been used to determine ionization constants and enthalpies of reaction for the protonation of the amino and carboxylate groups of several amino acids at temperatures of up to 125°C (Izatt et al, 1992;Gillespie et al, 1995;Wang et al, 1996). Vibrating-tube densimeters and a Picker-type flow microcalorimeter have recently been used to determine experimental values for the standard partial molar volumes and heat capacities of glycine, ␣-alanine, ␤-alanine, proline, and the dipeptide glycyl-gylcine, at temperatures as high as 275°C (Hakin et al, 1995(Hakin et al, , 1998Clarke and Tremaine, 1999;. We are aware of no other experimental studies on the thermodynamic properties of aqueous amino acids or peptides above 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…The values of C ∞ p,m,φ for aqueous solutions of glycine and glycylglycine used in these fits were those obtained at p = 0.1 MPa by Hakin et al (48,49) and the values of C ∞ p,m,φ (corr) reported in table 4. Estimates of the c 1 and c 2 coefficients and their standard errors for aqueous glycine and glycylglycine solutions are contained in table 6 together with estimates of the other coefficients for equation (20).…”
Section: Discussionmentioning
confidence: 86%
“…(25,48,49) To compare the present results with those previously reported, the following thermodynamic relation can be used:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations